Autekologi sebagai Tahapan Awal Rehabilitasi Ekosistem Mangrove Cuku Nyinyi, Desa Sidodadi, Kecamatan Teluk Pandan, Pesawaran - Chalida Syari; Budhi Agung Prasetyo; Mohammad Ashari Dwiputra (Yayasan Literasi Sains Indonesia, 2024)
The presence of mangroves tends to decrease every year, one of the reasons being degradation due to land cultivation. Mangrove rehabilitation activities are crucial to maintain the mangrove ecosystem sustainability. Cuku Nyinyi Mangrove located in Sidodadi Village, Teluk Pandan District, Pesawaran Regency. This ecosystem plays a vital role for both resident and migratory wildlife, living among the roots of mangrove trees. This research represents the initial phase of mangrove rehabilitation activities, focusing on autecology, which includes the analysis of reproductive patterns, normal hydrological patterns, and the biophysical condition of the mangrove ecosystem. The study utilizes primary and secondary data collection from three different mangrove zones. The sampling technique involves the transect line spot method. The reproductive pattern of mangroves in all three zones of Cuku Nyinyi Mangrove is dominated by the Rhizophora sp., with propagules as the type of seeds. The normal hydrological pattern for the tidal zone type is consistently inundated with a tree height ranging from 1.6 meters to 7 meters. The biophysical condition of the mangrove ecosystem in the three zones shows a salinity range from 25 to 33 ppt, temperature ranging from 25 °C to 29 °C, and pH levels from 7.2 to 7.8.